2016
DOI: 10.4081/jlimnol.2016.1220
|View full text |Cite
|
Sign up to set email alerts
|

The habitat type and trophic state determine benthic macroinvertebrate communities in lowland shallow lakes of China

Abstract: Benthic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…Downstream of the Yangtze River, China, most records from Lake Taihu 12 , 24 , 27 , Lake Hongze 14 , and Lake Chaohu 13 .…”
Section: Taxonomymentioning
confidence: 99%
“…Downstream of the Yangtze River, China, most records from Lake Taihu 12 , 24 , 27 , Lake Hongze 14 , and Lake Chaohu 13 .…”
Section: Taxonomymentioning
confidence: 99%
“…By managing the vegetation, one can maintain the reservoirs (or parts of them) in various stages of succession: the effects of this have been positive in the case of fish ponds (Buczyńska et al, 2007) and peat pools (Wildermuth, 2001). The present work, like the survey of the macrofauna of three shallow lakes in China (Hu et al, 2016), has shown that particular assemblages are associated with a specific level of productivity in a water body. This knowledge can be used to detect rising levels of eutrophication, one of the more serious problems affecting standing waters, which are also detrimental to biotic communities (Strayer and Dudgeon, 2010).…”
Section: Storage Reservoirs à Importance For Aquatic Fauna and Practimentioning
confidence: 57%
“…Weatherhead and James (2001) found positive relationships between Trichoptera and macrophyte biomass in the littoral zone of nine New Zealand lakes, and Tolonen et al (2003) discovered that Trichoptera in three lakes in Finland were significantly affected by macrophytes. In general, macrophytes in shallow lakes support more ecological niches, which in turn allows more species to coexist (Hu et al, 2016). The elodeid zone of lakes is more stable, with fewer incidental species and a large number of limnobionts in comparison with the helophyte zone (Czachorowski, 1998).…”
Section: Three-level Spatial Factors Influencing the Distribution Of mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Pan et al () revealed that macroinvertebrate diversity declined with increasing eutrophication in Yangtze lakes, because of the gradual disappearance of aquatic vegetation that provided food sources and habitable area for epiphytic animals. However, Hu et al () indicated that the total abundance of sediment microinvertebrates was significantly higher in the algae‐dominated lakes than in the macrophyte‐dominated lakes in eastern China. In this study, the diversity and abundance of denitrifying microbial communities did not differ significantly between macrophyte‐rich and macrophyte‐free lakes (Table ).…”
Section: Discussionmentioning
confidence: 99%